EFFECTS OF FLY ASH ADDITIVE ON THE PROPERTIES OF RAILWAY COMPOSITE DISC BRAKE LININGS - Akagunduz, Eyup; Topuz, Ahmet; Gunes, Mehmet (YILDIZ TECHNICAL UNIV, 2014)
Brake friction materials should satisfy a number of requirements such as stable friction coefficient, low wear rate, environmentally friendly, lightweight, long life, low noise, corrosion resistance and acceptable cost versus performance characteristics. Fly ash is an important side product, which accumulates in cyclone or electro filters through chimney gases occurring as a result of the combustion of pulverized coal in thermal power plants. In Turkey, approximately 45 million tons of coal is combusted annually and an average of 15 million tons of fly ash is produced. World annual production of fly ash is about 600 million tons. Fly ash which results from the coal-operated power plants causes economic and environmental problems. Fly ash particles are suitable for using in the brake linings of railway as a filler material. Waste fly ashes which contain compositions of Al2O3, SiO2, Fe2O3 from thermal power plants are used as brake lining. Many studies have been undertaken to show that adding the environmentally harmful waste to lining material could be used in a cost reducing way. In this study, the fly ash obtained from coal-fired thermal power plant Orhaneli and Kemerky was used. Our recent study has focused on development and utilization of fly ash for railway frictional composites. Produced composites brake linings contain 40% fly ash in weight ratio from Kemerky and Orhaneli. We compared the frictional and wear behavior of fly ash reinforced composite brake linings are compared on a commercial railway disk brake lining. The new developed brake linings have exhibited consistent properties; density of 1,79-2,18 g/ cm(3), hardness of 107-112 Hardness Rockwell L (HRL), modulus of elasticity in compression of 376-448 MPa, internal shear strength 15-46 MPa, and coefficient of friction 0,353-0,417.
Keywords: Railway brake linings; tribology; friction; fly ash; Engineering